The effect of physical activity on mood - a review of current literature - Łakomski, Mateusz; Pietsch, Julia; Chłystek, Joanna; Abramczyk, Agata; Golus, Anna; Zukow, Walery (Journal of Education, Health and Sport, 2017)
The impact of physical activity on human health has many benefits. Equally important in improving physical fitness and normalizing cardiovascular system seems to be the impact of exercise on mood of patients. Physical activity improves well-being, satisfaction and self-confidence. However, the condition of effective therapeutic intervention is due to its regularity, since only systematic exercises allow to maintain the beneficial effects of physical activity. Otherwise, the results achieved are only temporary. This article aims to review the current literature and show the most important aspects of motion therapy in improving the psychophysical condition of patients.